Antibody Response in The Blood of Cantang Grouper Infected by Viral Nervous Necrosis with Recombinant Protein Chlorella Vulgaris Vaccination - Choirul Huda; Uun Yanuhar; Muhammad Musa; Yusuf Wahyudi; Nur Sakinah Junirahma; Nico Caesar (Department of Aquaculture, 2023)
Cantang grouper (Epinephelus sp.) is one of the Export Oriented commodities which is a mainstay in increasing Indonesian mariculture production. The disease that causes many deaths in cantang grouper is Viral Nervous Necrosis. One of the most effective ways is by giving vaccines to fish. This study aims to develop a recombinant protein Chlorella vulgaris vaccine with the addition of an adjuvant to increase the immunity of cantang grouper infected with VNN. The method used was experimental with a Completely Randomized Design (CRD) consiting of seven treatments and three replications, namely (K+) cantang grouper infected with VNN, (T1) Healthy cantang grouper was given 33 µl of vaccine, (T2) Healthy cantang grouper was given vaccine of 66 µl, (T3) Healthy cantang grouper was given 112 µl of vaccine, (T4) Healthy cantang grouper was given 33 ul of vaccine and then tested against Viral Nervous Necrosis, (T5) Healthy cantang grouper was given 66 ul vaccine and then tested against Viral Nervous Necrosis, (T6) Healthy cantang grouper was given 112 ul vaccine and then tested against Viral Nervous Necrosis. The fish used were 8-10 cm in size and were reared for 56 days. The results showed that the Chlorella vulgaris protein recombinant vaccine with the addition of adjuvant gave a very significant effect on the immunity of cantang grouper infected with VNN with the best dose of 33 µl (T4) seen from the relative protection level (RPS) (75,6%), survival of cantang grouper (78%) after challenge test and a significant increase in antibody titer.